(untitled) (Research, Society and Development, 2023)
Lifestyle represents a set of everyday actions reflected in people’s attitudes and values. During the pandemic, there was a reduction in the time used for physical activity and changes in eating habits, possibly resulting in an increase in sedentary behavior and negatively affecting the body mass index (BMI) of university students in the northern region of Brazil. The objective was to identify the influence of lifestyle on the BMI of university students in the northern region of Brazil, during social isolation caused by the COVID-19 pandemic. This was a cross-sectional observational study, comprising 432 undergraduate and graduate students from public and private universities, of both sexes, with a mean age of 26.2 ± 8.6 years. Lifestyle was verified using the questionnaire “Estilo de Vida Fantástico’’ Brazilian version conducted by Añez, Reis & Petroski (2008), being classified in points, being Excellent (85-100), Very good (70-84), Good (55-69), Fair (35-54) and Needs Improvement (0-34). BMI was calculated by the ratio between body mass and height squared. Participants were classified into Underweight, Normal Weight, Overweight and Obesity. The influence of lifestyle on BMI was verified using the chi-square test, with an alpha error of 5%. There were statistically significant associations between lifestyle and BMI with P = 0.003. The findings suggest that lifestyle influences the BMI of university students, showing that students classified as having a good lifestyle had normal BMI.